The Paul-Apollos relationship and Paul's stance toward Greco-Roman rhetoric : an exegetical and socio-historical study of 1 Corinthians 1-4 /: an exegetical and socio-historical study of 1 Corinthians 1-4. (©2009) - Unknown
No abstract available